Genetic gain as a result of corn cultivars annual substitution - Storck, Lindolfo; Bisognin, Dílson Antônio; Filho, Alberto Cargnelutti (Pesquisa Agropecuaria Brasileira, 2005)
<!–[if gte mso 9]> Normal 0 <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; p.MsoTitle, li.MsoTitle, div.MsoTitle margin:0cm; margin-bottom:.0001pt; text-align:center; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Arial; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:PT-BR; font-weight:bold; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> Corn (Zea mays) cultivars are usually replaced a few years after release. The objective of this study was to evaluate a proposed hypothesis test to determine if the annually cultivars replacements, in comparative field trials of recommended corn cultivars, result in genetic gain of grain yield. Comparative field trials of super early, early and normal corn cultivars were carried out during 1998/1999, 1999/2000, 2000/2001 and 2001/2002 grown seasons. The experimental design was a complete randomized block with three replications. Each plot had two rows of 5 m separated by 0.8 m. Grain yield genetic gain was estimated by the Vencovsky et al. method. Genetic gain significance was verified with the proposed hypothesis test. The annual replacement of corn cultivars is a dynamic process that not always result in genetic gain of grain yield.